2012
DOI: 10.1038/aja.2011.166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melandrium firmum methanolic extract on testosterone-induced benign prostatic hyperplasia in Wistar rats

Abstract: Benign prostatic hyperplasia (BPH) is an age-related disease of unknown aetiology characterized by prostatic enlargement coincident with distinct alterations in tissue histomorphology. Instead of therapeutic agents that can cause severe side effects, plant extracts are frequently used to treat BPH. In this study, we investigated whether the Melandrium firmum methanolic extract (MFME) improves BPH, using the testosterone propionate (TP)-induced BPH rat model. Castration was performed via the scrotal route under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
6
32
1
Order By: Relevance
“…37) Animals with experimentally induced BPH also have significantly increased prostatic PCNA expression. 38,39) We found that rats with BPH that were given QI treatment had significantly reduced expression of PCNA and cyclin D1, as well as fewer PCNA-positive cells. This indicates that QI protected against BPH development due to its anti-proliferative activity.…”
Section: Discussionmentioning
confidence: 82%
“…37) Animals with experimentally induced BPH also have significantly increased prostatic PCNA expression. 38,39) We found that rats with BPH that were given QI treatment had significantly reduced expression of PCNA and cyclin D1, as well as fewer PCNA-positive cells. This indicates that QI protected against BPH development due to its anti-proliferative activity.…”
Section: Discussionmentioning
confidence: 82%
“…Androgens and oestrogens significantly influence the development of benign prostatic hyperplasia. However, the prostate needs androgens for normal physiological functioning and concentration of these hormones in excess of the physiological threshold may result in aberrant growth of the prostate (Lee et al, 2012). An alternative pharmacological approach in patients with BPH is to inhibit the androgens responsible for prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…), and MeJA (50 mg/kg i.p.) were given daily to the animals for 4 consecutive weeks (Umukoro and Olugbemide, 2011;Lee et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Glutathione reductase, a flavoprotein enzyme, regenerates GSH from GSSG, with NADPH as a source of reducing power. Increase in the levels of lipid peroxidation and decrease in antioxidants have been detected in BPH (Lee et al, 2012). In BPH rats, intake of some herbal extracts has been reported to reduce oxidative stress (Siddiqui et al, 2005;Prasad et al, 2008;Hevesi et al, 2009;Lopez et al, 2009).…”
mentioning
confidence: 99%